Comparison of the Physiological Properties of Human Periodontal-Masseteric Reflex Evoked by Incisor and Canine Stimulation - Ohmori, Hiroko; Kirimoto, Hiroaki; Ono, Takashi (Frontiers in Physiology, 2012)
Introduction: The present study was designed to clarify whether the bilateral cooperation in the human periodontal-masseteric reflex (PMR) differs between central incisors and canines. Methods: Surface array electrodes were placed on the bilateral masseter muscles to simultaneously record the firing activities of single motor units from both sides in seven healthy adults. During light clenching, mechanical stimulation was applied to the right maxillary central incisor and canine to evoke the PMR. Unitary activity was plotted with respect to the background activity and firing frequency. The slope of the regression line (sRL) and the correlation coefficient (CC) between the central incisor and canine and the lateral differences between these values were compared. Results: There were significant differences in the sRL and CC, as well as lateral differences, between the central incisor- and canine-driven PMR. Discussion: These results suggest that the PMR differs depending on both the tooth position and laterality.